2015
DOI: 10.1097/mib.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

PedsQL Gastrointestinal Symptoms Scales and Gastrointestinal Worry Scales in Pediatric Patients with Inflammatory Bowel Disease in Comparison with Healthy Controls

Abstract: The PedsQL Gastrointestinal Symptoms and Worry Scales may be used as common metrics across pediatric patients with IBD, including Crohn's disease and ulcerative colitis separately to measure gastrointestinal-specific symptoms in clinical research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
1
36
1
1
Order By: Relevance
“…Chouliaras et al [25] reported in pediatrics, CD patients had better QoL than UC patients although they did not reach statistical significance. Another pediatric study reported there were no significant differences in the quality of life (PedsQL) scores between pediatric CD and UC [38]. In contrast, this present finding demonstrated patients with CD had a significantly better QoL than patients with UC in terms of the physical well-being, emotional well-being, school performance, self-esteem, family, prolong illness, and total QoL score (KINDL R score).…”
Section: Discussioncontrasting
confidence: 87%
“…Chouliaras et al [25] reported in pediatrics, CD patients had better QoL than UC patients although they did not reach statistical significance. Another pediatric study reported there were no significant differences in the quality of life (PedsQL) scores between pediatric CD and UC [38]. In contrast, this present finding demonstrated patients with CD had a significantly better QoL than patients with UC in terms of the physical well-being, emotional well-being, school performance, self-esteem, family, prolong illness, and total QoL score (KINDL R score).…”
Section: Discussioncontrasting
confidence: 87%
“…4,5 Although IBD is not believed to have a psychosocial origin, a number of studies have identified psychosocial variables associated with the disease, 6-8 some of which clearly have the potential for significantly affecting the quality of life of IBD patients. 9-11 Comparing children with IBD to matched controls, researchers have found more anxiety, depression, social functioning (inter-personal interactions in social situations) problems and family dysfunction in those with IBD. 7 Many studies have found depression in particular is increased in youth with IBD compared to controls 7 and parents of children with IBD also show increased levels of depression.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough QOL evaluation should include the evaluation of all of these dimensions. Varni et al have also developed numerous disease specific scales [22][23][24][25][26] . A cancer module of PedsQL is also available for children with cancer 19 .…”
Section: Discussionmentioning
confidence: 99%